2014
DOI: 10.1177/0261927x14526993
|View full text |Cite
|
Sign up to set email alerts
|

Um . . . Who Like Says You Know

Abstract: Filler words (I mean, you know, like, uh, um) are commonly used in spoken conversation. The authors analyzed these five filler words from transcripts recorded by a device called the Electronically Activated Recorder (EAR), which sampled participants' language use in daily conversations over several days. By examining filler words from 263 transcriptions of natural language from five separate studies, the current research sought to clarify the psychometric properties of filler words. An exploratory factor analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…A growing body of research in psychology examines differences in language use between demographic and social groups using either closed-vocabulary lexicons (Laserna, Seih, & Pennebaker, 2014;Yarkoni, 2010) such as the program Linguistic Inquiry and Word Count (LIWC; Pennebaker, Mehl, & Niederhoffer, 2003;Tausczik & Pennebaker, 2010), or open-vocabulary approaches (e.g., Schwartz et al, 2013). Most of these analyses aim to identify differences in language features between mutually exclusive groups (e.g.…”
Section: Social Identity and Language Usementioning
confidence: 99%
“…A growing body of research in psychology examines differences in language use between demographic and social groups using either closed-vocabulary lexicons (Laserna, Seih, & Pennebaker, 2014;Yarkoni, 2010) such as the program Linguistic Inquiry and Word Count (LIWC; Pennebaker, Mehl, & Niederhoffer, 2003;Tausczik & Pennebaker, 2010), or open-vocabulary approaches (e.g., Schwartz et al, 2013). Most of these analyses aim to identify differences in language features between mutually exclusive groups (e.g.…”
Section: Social Identity and Language Usementioning
confidence: 99%
“…Shriberg (2001) also reported that men used more filled pauses than women [16]. Laserna et al (2014), however, found that filled pauses were used at comparable rates across genders and age, whereas discourse markers (I mean, you know, like) were more common among women, younger speakers, and more conscientious speakers [17].…”
Section: Introductionmentioning
confidence: 99%
“…1 B). Fillers were defined as an extraneous word or set of words (e.g., “uh”, “um”, “y’know”, or “well” 1 , 38 ). We used Cool Edit Pro version 2 (Syntrillium Software Corp., Phoenix, AZ, USA) to aid in the manual marking of each phrase of interest 39 .…”
Section: Methodsmentioning
confidence: 99%
“…Regardless of age, gender, or native language, healthy individuals use filler phrases, also known as filled pauses, during spontaneous speech 1 . Frequent utterance of fillers is tightly associated with increased effort to recall or search for a relevant word 2 , increased anxiety 3 , and divided attention 4 .…”
Section: Introductionmentioning
confidence: 99%